2019
DOI: 10.1016/j.rbmo.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

High proportion of immature oocytes in a cohort reduces fertilization, embryo development, pregnancy and live birth rates following ICSI

Abstract: earned a Master's degree in Biology from University of Sannio in 2015. She is a clinical embryologist with an academic faculty position at Weill Cornell Medicine. She is currently conducting several research projects on male infertility. One such project aims at measuring sperm chromatin fragmentation (SCF) from different levels of the male genital tract. In men with high SCF, Alessandra is isolating spermatozoa through a microfluidic device yielding the highest portion of progressively motile cells characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Failure to yield an optimal maturation rate entails that some oocytes remain at either the germinal vesicle (GV) or metaphase I (MI) stages [37]. Thus, the proportion of MII oocytes retrieved can be affected by follicle size, ovarian stimulation protocols, or the surgeon's ability to retrieve the smallest antral follicle [209]. An assessment of couples with low fertilization found that standard in vitro insemination was not beneficial in achieving higher fertilization rates in subsequent cycles [210].…”
Section: Low Oocyte Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to yield an optimal maturation rate entails that some oocytes remain at either the germinal vesicle (GV) or metaphase I (MI) stages [37]. Thus, the proportion of MII oocytes retrieved can be affected by follicle size, ovarian stimulation protocols, or the surgeon's ability to retrieve the smallest antral follicle [209]. An assessment of couples with low fertilization found that standard in vitro insemination was not beneficial in achieving higher fertilization rates in subsequent cycles [210].…”
Section: Low Oocyte Maturitymentioning
confidence: 99%
“…Indeed, a recent study evaluating oocyte maturity allocated 7672 ICSI cycles according to their oocyte nuclear maturity ratios. The minimal maturation cohort, characterized by the highest proportion of MI and GV oocytes, displayed significantly lower normal 2PN fertilization, implantation, and clinical pregnancy rates, indicating an association of the low number of mature oocyte within the cohort with oocyte readiness to be fertilized [209]. The utilization of ICSI would allow for a more detailed information on the response of a patient to a specific superovulation protocol.…”
Section: Low Oocyte Maturitymentioning
confidence: 99%
“…Superovulation protocols aimed at achieving a higher proportion of metaphase 2 (MII) oocytes would also be effective in achieving better fertilization and pregnancy outcomes (12). It has also been shown that fertilization rates and embryo developmental competence of inseminated oocytes are directly related not only to nuclear but to ooplasmic and membrane maturity (13,14), indicating that for fertilization to occur, oocytes must have a responsive mature cytoplasm capable of generating proper Ca 2þ oscillation patterns after sperm exposure.…”
mentioning
confidence: 99%
“…The goal of oocyte cryopreservation is generally to freeze mature oocytes for later thawing and fertilization with IVF (Lee et al, 2013). However, 8.6% to 20% of the oocytes retrieved after controlled ovarian stimulation are metaphase I (MI) or immature at the germinal vesicle (GV) (Beall et al, 2010;Parrella et al, 2019), with total failure in oocyte maturation occurring occasionally, leading to no mature oocytes being produced (Beall et al, 2010). Successful fertilization depends on synchronic cytoplasmic and nuclear maturation (Pereira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Successful fertilization depends on synchronic cytoplasmic and nuclear maturation (Pereira et al, 2016). There is evidence that an increased proportion of immature oocytes (GV and MI) diminish the ability of the MII sibling oocytes to be normally fertilized, resulting in a diminished number of good-quality embryos (Parrella et al, 2019).…”
Section: Introductionmentioning
confidence: 99%